Analisis Komparatif Kinerja Keuangan Berdasarkan Rasio Profitabilitas, Likuiditas, dan Solvabilitas Pada PT AKR Corporindo Tbk Dan PT Elnusa Tbk Periode 2010-2024 - Adani, Achmad Adzim; Puji Muniarty (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze and compare the financial performance between PT AKR Corporindo Tbk and PT Elnusa Tbk based on liquidity, profitability, and solvency ratios. The research question addressed in this study is whether there are differences in financial performance between the two companies as measured by the Current Ratio, Return on Assets (ROA), and Debt to Asset Ratio. The research method used is a quantitative method with a comparative analysis approach. The data used are secondary data obtained from the companies’ annual financial statements over a 15-year period. The data collection technique is documentation by collecting data from the statement of financial position and income statement. The results of this study are expected to show differences in the level of financial performance between the two companies in terms of liquidity, profitability, and solvency. These differences may reflect variations in financial conditions and financial management strategies implemented by each company. This study is expected to provide contributions to investors, management, and other stakeholders in decision-making, as well as serve as a reference for evaluating financial performance based on financial statements.